Maternal DNMT3A-dependent de novo methylation of the paternal genome inhibits gene expression in the early embryo - Richard Albert, Julien; Au Yeung, Wan Kin; Toriyama, Keisuke; Kobayashi, Hisato; Hirasawa, Ryutaro; Brind’Amour, Julie; Bogutz, Aaron; Sasaki, Hiroyuki; Lorincz, Matthew (Nature communications, 2020)
De novo DNA methylation (DNAme) during mammalian spermatogenesis yields a densely methylated genome, with the exception of CpG islands (CGIs), which are hypomethylated in sperm. While the paternal genome undergoes widespread DNAme loss before the first S-phase following fertilization, recent mass spectrometry analysis revealed that the zygotic paternal genome is paradoxically also subject to a low level of de novo DNAme. However, the loci involved, and impact on transcription were not addressed. Here, we employ allele-specific analysis of whole-genome bisulphite sequencing data and show that a number of genomic regions, including several dozen CGI promoters, are de novo methylated on the paternal genome by the 2-cell stage. A subset of these promoters maintains DNAme through development to the blastocyst stage. Consistent with paternal DNAme acquisition, many of these loci are hypermethylated in androgenetic blastocysts but hypomethylated in parthenogenetic blastocysts. Paternal DNAme acquisition is lost following maternal deletion of Dnmt3a , with a subset of promoters, which are normally transcribed from the paternal allele in blastocysts, being prematurely transcribed at the 4-cell stage in maternal Dnmt3a knockout embryos. These observations uncover a role for maternal DNMT3A activity in post-fertilization epigenetic reprogramming and transcriptional silencing of the paternal genome. The paternal genome in mice undergoes widespread DNA methylation loss post-fertilization. Here, the authors apply allele-specific analysis of WGBS data to show that a number of genomic regions are simultaneously de novo methylated on the paternal genome dependent on maternal DNMT3A activity, which induces transcriptional silencing of this allele in the early embryo.